Log in to add a comment

Log in to add a comment

taking log on both side

ln y = ln y^cot^-1x^4)^7

lny=(cot^-1x^4)lny

1/y dy/dx = (cot^-1x^4 )^7. d/dx lny + y .d/dx (cot^-1x^4)^7

1/y dy/dx = (cot^-1x^4)^7 . 1/y dy/dx + y ( 7 cot-x^4)^6 . d/dx (cot ^-x^4)

1/y dy/dx=(cot^-1x^4)^7.1/y dy/dx + y(7 cot^-x^4)^6. (-1/1+(x^4)^2 . d/dx x^4

1/y dy/dx =(cot ^-1 x^4)^7 . 1/y dy/dx + y(7 cot^-x^4)^6(-1/1+(x^4)^2).4x^3

1/y . dy/dx - 1/y.dy/dx (cot^-1x^4)^7= y(7 cot^-x^4)^6(-1/1+(x^4)^2).4x^3

dy/dx{1/y - 1/y.dy/dx (cot^-1x^4)^7} = y(7 cot^-x^4)^6(-1/1+(x^4)^2).4x^3

dy/dx =[y(7 cot^-x^4)^6(-1/1+(x^4)^2).4x^3]÷{1/y - 1/y.dy/dx (cot^-1x^4)^7}

hence find this differentation toooooooooo hard finally i solve thi :)